Frequency of two VKORC1 gene variants and its correlation with warfarin maintenance dose - esmat khaleqsefat; Mohammad Khalaj-Kondori; Morteza Jabbarpour bonyadi; Hamid Soraya; Behnam Askari (یافته‌های نوین در علوم زیستی, 2018)
Warfarin is a commonly-prescribed anticoagulant used to treat and prevent thromboembolic events. The requirement for varying doses of warfarin depends on genetic and environmental components. In this study, the frequency of two single-nucleotide polymorphic variants of the vitamin K epoxide reductase complex subunit 1 (VKORC1) gene (1173 C>T (rs9934438) and 3730 G>A (rs7294)) and its correlation with warfarin maintenance doses were investigated in patients with heart valve replacement from West Azarbayejan, Iran. Blood samples were obtained from 185 patients; their genomic DNA was extracted and samples were genotyped by polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) assay. To assess if the blood warfarin level is different among genotypes, we used a one-way analysis of variance (ANOVA) followed by a Tukey’s post-hoc comparison. The minor allele frequency was determined to be 54% for 1173T and 53.7% for 3730A. Patients who carried the G allele at position 3730 and T allele at position 1173 required a significantly lower daily mean warfarin dosage (P <0.001). Consideration of the VKORC1 gene polymorphism, especially at the initial stages of the therapy, can be helpful in pre-treatment dosing of warfarin, which, in turn, reduces the adverse effects resulting from inappropriate drug prescription.